2002
DOI: 10.1002/jbm.10083
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of modern dentin adhesives—in vitro testing on gingival fibroblasts

Abstract: The present investigation was designed to test cellular toxicity of modern dentin adhesives. With the use of the products Ariston Liner, Etch & Prime 3.0, Optibond Solo, Prime & Bond NT, Scotchbond 1, and Syntac Sprint, test specimens were prepared according to the manufacturers' instructions and transferred into a culture medium. Eluates were obtained and pipetted onto fibroblast cultures, incubated, and subsequently stained. The respective cell densities and the numbers of normal, altered, and dead cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…52,53 Previous studies also demonstrated that modern dentine adhesives, including Prime & Bond NT, exhibit cellular toxicity. 54,55 In the current study, the result of the MTT assay was consistent with those of previous studies. However, the addition of TEGDMA nanocapsules to this commercial adhesive did not affect cellular toxicity, indicating that TEGDMA nanocapsules met the biocompatibility requirements in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…52,53 Previous studies also demonstrated that modern dentine adhesives, including Prime & Bond NT, exhibit cellular toxicity. 54,55 In the current study, the result of the MTT assay was consistent with those of previous studies. However, the addition of TEGDMA nanocapsules to this commercial adhesive did not affect cellular toxicity, indicating that TEGDMA nanocapsules met the biocompatibility requirements in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that, these restorative materials contain a great variety of monomers and additives (18). Some of these components, owing to the complex chemical composition and incomplete monomer-polymer conversion, leach out from resin-based restorative materials into the oral environment (55,57). Such leaching may cause adverse effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…bonding agent that contained "is-GM" was less cytotoxic than the other bonding agents that contained "is-GM" + UDM" + HEM" and "is-GM" + HEM" [ 0]. In addition, it was demonstrated that a combination of "is-GM" and HEM" was less cytotoxic than a combination of the following three substances: "is-GM", UDM", and HEM" [12]. HEM" is the most frequent hydrophilic monomer present in adhesive systems.…”
Section: In Vitro Biocompatibility Testings Of Dental Adhesivesmentioning
confidence: 99%
“…The determinant factor of the death was the monomer concentration, given that low concentrations of "is-GM" induced apoptosis, whereas high concentrations induced death by necrosis or late apoptosis. "is-GM" dissolves easily and may cause irritation or a lichenoid reaction of the oral mucosa in close and prolonged contact with gingival tissues, especially after cervical illing procedures [12,66]. TEGDM" is a copolymer used in major recent biomaterials with resin phase as a diluent.…”
Section: In Vitro Biocompatibility Testings Of Dental Adhesivesmentioning
confidence: 99%